2014
DOI: 10.1002/wmh3.114
|View full text |Cite
|
Sign up to set email alerts
|

Morality Framing in U.S. Drug Control Policy: An Example From Marijuana Decriminalization

Abstract: The politics of so-called "morality policies" including same-sex marriage, abortion, gambling, and drug control have captured the attention of the public and social scientists in recent years. Drawing on data from journalistic accounts, legislative transcripts, elite interviews, and document analysis, this study examines the extensiveness of morality talk in debates over marijuana decriminalization in the United States. The results indicate that critics deployed moral (decriminalization sends the wrong message… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…By contrast, the practical appeal, entitled "Legalizing Marijuana: Unwise and Impractical," framed its antilegalization position in pragmatic terms (e.g., "In the rush to legalize, we haven't fully thought through some of the pragmatic consequences of legalization") and cited particular economic and pragmatic concerns (e.g., "Repealing current laws will generate additional costs due to increases in marijuana use and dependence"). Arguments were adapted from scholarly analyses of journalistic and legislative texts regarding marijuana decriminalization, which found that actual arguments made for this topic have appeal ed to both moral and instrumental concerns (Ferraiolo, 2014).…”
Section: Independent Variablesmentioning
confidence: 99%
“…By contrast, the practical appeal, entitled "Legalizing Marijuana: Unwise and Impractical," framed its antilegalization position in pragmatic terms (e.g., "In the rush to legalize, we haven't fully thought through some of the pragmatic consequences of legalization") and cited particular economic and pragmatic concerns (e.g., "Repealing current laws will generate additional costs due to increases in marijuana use and dependence"). Arguments were adapted from scholarly analyses of journalistic and legislative texts regarding marijuana decriminalization, which found that actual arguments made for this topic have appeal ed to both moral and instrumental concerns (Ferraiolo, 2014).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Broadly defined, morality policies are public policies involving conflicts about core moral issues that are salient to the general public and that lack technical complexity (Arsneault 2001; Ferraiolo 2014; Mooney and Lee 1995; Mooney and Schuldt 2008). They are distinct from nonmoral policies in that, typically, “at least one side of the debate frames the issue in terms of morality or sin, and the policies seek to validate one set of values at the expense of others” (Kreitzer 2015: 43).…”
Section: Conservatism and Support For Moral Regulation Lawsmentioning
confidence: 99%
“…In arguing that binding morality underlies support for moral regulation laws, it is important to note that public discussions about moral regulation rarely invoke concerns associated with Authority, Loyalty, or Sanctity. Rather, moral regulation laws are almost invariably framed as preventing harm to individual citizens (Burlone and Richmond 2018; Euchner et al 2013; Ferraiolo 2014; Gandsman 2016), even in internal communications among conservatives (Thomas 2013). Pornography entices consumers to rape innocent women (Lykke and Cohen 2015).…”
Section: Perceived Harm and Moral Regulation Lawsmentioning
confidence: 99%
“…In contrast, political conflict in latent morality policies can be, but certainly is not always dominated by moral frames and conflict about first principles. In areas like drug or gambling policy, for example, economic considerations as well as arguments about public health represent instrumental arguments that are often much more important to the political debate than moral arguments (Euchner, Heichel, Nebel, & Raschzok, ; Ferraiolo, ). Latent morality policies are hence based on multiple dimensions of conflict, which should facilitate negotiations and the easier identification of a compromise solution.…”
Section: Theory and Hypothesesmentioning
confidence: 99%